PEMPROGRAMAN WEB PENGUATAN DASAR DAN PELATIHAN PEMBUATAN WEB UNTUK SISWA/I SMK SUMPAH PEMUDA - Abdullah Muhajir; Tio Andrian (Journal of Research and Publication Innovation, 2025)
This community service activity aims to strengthen the basic understanding and improve the skills of Visual Communication Design (DKV) students at Sumpah Pemuda Vocational School in the field of web programming, especially through training in the use of HTML and CSS as a foundation for developing simple websites. The background of this program is based on the low technical digital literacy among DKV students, who are generally stronger in the visual design aspect but do not yet have the ability to implement design results into interactive and responsive web-based media. The method of implementing the activity uses a direct practice approach (learning by doing) with material that is arranged in stages, starting from an introduction to HTML structure, writing basic elements, to using simple CSS for the aesthetics of the page display. The activity was carried out in one day with intensively focused time, attended by grade X and XI DKV students. Evaluation was carried out through direct observation, individual practice assignments, and interviews with participants and accompanying teachers to assess the effectiveness of the approach and the achievement of the activity's objectives. The results of the activity showed that this training succeeded in answering four main focus problems: (1) students' low initial understanding of web programming; (2) the need for contextual training methods that are in accordance with the character of DKV students; (3) significant improvement in technical skills after training; and (4) identification of various learning challenges such as limited facilities, unfamiliarity with technical language, and fear of errors when typing code. Students are not only able to create simple web pages, but also show further interest in learning more complex web development technologies. This training provides an important contribution in building the foundation of digital competence for design-based vocational school students, and shows that the integration of visual creativity and programming skills is a strategic step in preparing graduates who are adaptive to the demands of the digital creative industry. This program also shows that with a humanistic, practical, and participatory approach, students can learn technology meaningfully and enjoyably in a relatively short time.